Intrauterine administration of endotoxin leads to motor deficits in a rabbit model: a link between prenatal infection and cerebral palsy - Saadani-Makki, Fadoua (2008)
OBJECTIVE: To determine whether maternal intrauterine endotoxin administration leads to neurobehavioral deficits in newborn rabbits. STUDY DESIGN: Pregnant New Zealand white rabbits were injected with 1ml saline (n=8) or 20μg/kg of lipolysaccharide in saline (LPS) (n=8) into the uterine wall on day 28/31 of gestation. On postnatal day 1, kits [saline (n=30) and LPS (n=18) from 4 consecutive litters] underwent neurobehavioral testing. Neonatal brains were stained for microglial cells and myelin. RESULTS: LPS-group kits were hypertonic and demonstrated significant impairment in posture, righting reflex, locomotion and feeding, along with neuroinflammation indicated by activated microglia, and hypomyelination in the periventricular regions. A greater mortality was noted in the LPS group (16 stillbirths from 3 litters vs. 3 from 1 litter). CONCLUSION: Maternal intrauterine endotoxin administration leads to white matter injury and motor deficits in the newborn rabbit resulting in a phenotype that resembles those found in periventricular leukomalacia and cerebral palsy.